POLA KOMUNIKASI INTERPERSONAL KEPALA SEKOLAH DAN GURU SMA INTERGRAL HIDAYATULLAH BATAM KEPULAUAN RIAU - Afifi Ubadillah; Agus Sujarwo; Garum (UNISAN JURNAL, 2025)
This study aims to analyze or find out how the principal's interpersonal communication is both directly and indirectly through five positive attitudes including openness, empathy, supportive attitude, positive attitude and equality, and can affect teacher work motivation through the fulfillment of human needs, namely physiological needs, security needs, social needs, appreciation needs and self-actualization needs. This type of research is a type of qualitative research. Data collection methods are carried out by means of observation, interviews, and documentation. Data analysis techniques by reducing data, presenting data, and drawing conclusions. Data validity testing is carried out through triangulation, transcription and data sources. The results of the study showed 1) Teachers at SMA Intrgral Hidayatullah Batam Kepulauan Riau felt that the work environment was safe, comfortable and clean. Most of the teachers and employees who work can also fulfill the need for social interaction, 2) The condition of teacher work motivation, namely the principal has implemented and carried out his duties as a manager by providing motivation and enthusiasm through direct interpersonal communication with teachers by fulfilling needs such as physiological needs, security, social, appreciation, and self-actualization. 3) The interpersonal communication patterns of the principal applied are oral interpersonal communication patterns (directly) and written interpersonal communication (indirectly)